Understanding the management logic of private forest owners: a new approach - Novais, Ana (2010)
Recently, several typologies of non-industrial private forest owners were established in order to assess their objectives and attitudes toward forests. However, current management practices and work organization have usually not been explicitly addressed in these empirically based typologies. In a context of increasing outsourcing and decreasing family work in forests, it is important to know the forest practices, who carries them out, and with whose labour and equipment. The interrelated knowledge of these variables sheds light on the constraints faced by different forest owners and about the agents caring for their forests. Such knowledge can also improve the understanding of forest owners' behaviour and, therefore, be useful for the design and implementation of forest policies. The work models of Portuguese non-industrial private forest were identified with these goals in mind. A cluster analysis, using a representative nationwide sample and an empirically based set of variables, was instrumental in identifying six work models. The interrelation amongst these models and other variables such as landholding attributes (e.g. forest size and dominant species), owners' social profile, and their economic goals was also assessed. Finally, the main dynamics of private owners' forest management are outlined.